Corrosion-induced tin whisker growth in electronic devices: a review. Issue 1 (6th February 2017) - Illés, Balázs; Horváth, Barbara; Géczy, Attila; Krammer, Olivér; Dušek, Karel
Abstract : Purpose: The aim of this paper is to present a review of the tin whisker growth phenomena. The study focuses mainly on whisker growth in a corrosive climate when the main inducing factor of the whisker growth is oxidation. The tin whisker phenomenon is still a big challenge in lead-free reflow soldering technology. Modern lead-free alloys and surface finishes with high tin content are considered to be possible sources of whisker development, also the evolution of electronic devices towards further complexity and miniaturization points to an escalation of the reliability risks. Design/methodology/approach: The present work was based on a worldwide literature review of the substantial previous works in the past decade, as well as on the results and experience of the authors in this field. Findings: The effect of corrosion on tin whisker growth has been under-represented in reports of mainstream research; however, in the past five years, significant results were obtained in the field which raised the corrosion phenomena from being a side effect category into one of the main inducing factors. This paper summarizes the most important findings of this field. Practical implications: This literature review provides engineers and researchers with a better understanding of the role of corrosion in tin whisker growth and the current challenges in tin whisker mitigation. Originality/value: The unique challenges and future research directions about the tin whisker phenomenon were shown to highlight rarely discussed risks and problems in lead-free soldering reliability.